OLAHRAGA SEBAGAI PENDORONG GAYA HIDUP SEHAT DI MASYARAKAT: TINJAUAN LITERATUR - Siregar, Yan Indra; Arima, Putra; Fitria, Yeni; Nasution, Iman Ali Matua; Salim, Yoga Dwi; Hsb, Sholahuddin Ramadan; Rabbani, Muhammad Priya; Anggian, Arista; Ardiansyah, Riko; Malau, Jeremi Jordan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of modern lifestyles, which tend to be physically inactive, has led to various health problems in society, including an increased risk of chronic diseases and decreased quality of life. Therefore, exercise plays an important role in promoting a healthy lifestyle. This study aims to analyze the role of exercise in encouraging healthy living through a literature review method. The data were obtained from 10 national journals published within the last 5 to 10 years and relevant to the research topic. The analysis technique used was content analysis by comparing findings from various studies. The results indicate that exercise has a significant impact on improving physical fitness, mental health, and public awareness in adopting healthy lifestyles. However, several challenges remain, such as lack of motivation, limited time, and insufficient facilities, which hinder community participation in physical activities. Therefore, continuous efforts through education, health programs, and environmental support are needed to make exercise a consistent habit in daily life. Keywords: exercise, healthy lifestyle, physical activity